2010
DOI: 10.3390/ijerph7031093
|View full text |Cite
|
Sign up to set email alerts
|

Beer and its Non-Alcoholic Compounds: Role in Pancreatic Exocrine Secretion, Alcoholic Pancreatitis and Pancreatic Carcinoma

Abstract: In this article we provide an overview of the newest data concerning the effect of non-alcoholic constituents of alcoholic beverages, especially of beer, on pancreatic secretion, and their possible role in alcoholic pancreatitis and pancreatic carcinoma. The data indicate that non-alcoholic constituents of beer stimulate pancreatic enzyme secretion in humans and rats, at least in part, by direct action on pancreatic acinar cells. Some non-alcoholic compounds of beer, such as quercetin, resveratrol, ellagic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 47 publications
0
23
0
1
Order By: Relevance
“…It has been shown to reduce the incidence of a variety of carcinogen-induced tumors 20 . The anticarcinogenic effect of EA was shown in several types of cancers [21][22][23][24][25] . In our study we observed, EA at 25-200µM strikingly reduced the cell viability of U251 cells, suggesting the anti-proliferative efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to reduce the incidence of a variety of carcinogen-induced tumors 20 . The anticarcinogenic effect of EA was shown in several types of cancers [21][22][23][24][25] . In our study we observed, EA at 25-200µM strikingly reduced the cell viability of U251 cells, suggesting the anti-proliferative efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol, another polyphenol, reversed the abnormal Ca 2+ signal induced by treatment with cerulein, and also reduced the histological damage induced by the agonist, as well as hyperamylasemia and hyperlipidemia (Carrasco et al, 2014). These and other compounds present in beverages, such as quercetin, ellagic acid, or catechins, have been shown to be protective against pancreatitis by controlling pancreatic secretion, by stellate cell activation, or by reducing oxidative stress (Gerloff et al, 2010).…”
Section: +mentioning
confidence: 99%
“…Nowsze badania wskazują, że jedynym napojem, który ewidentnie stymuluje egzokrynną sekrecję trzustkową, jest piwo [86]. Za ten efekt mają być odpowiedzialne zawarte w nim, jeszcze niezidentyfikowane, składniki niealko-holowe [87][88][89]. Zdaniem badaczy japońskich jednym z takich związków może być N-metylotyramina [90].…”
Section: Wpływ Napojów Alkoholowych Na Trzustkęunclassified